Environmental Sustainability and Business Feasibility of Digital Platforms: A Sharia-Based Approach - Reny Fitriana Kaban; Natasya Amelia Yupita; Najwa Tsalisa Karim (Journal of Business, Finance, and Banking, 2026)
The rapid expansion of digital platform ecosystems has played a crucial role in promoting economic inclusion and innovation, particularly in emerging economies. However, this growth has also generated significant environmental challenges that are often overlooked in conventional business feasibility assessments. This study aims to analyze the environmental impacts of PT GoTo Gojek Tokopedia Tbk (GoTo) and to evaluate its business feasibility through an integrated sharia-based perspective. Methods: This research employs a qualitative descriptive approach by integrating Environmental Impact Assessment (AMDAL), SWOT analysis, and maqashid shariah as a normative ethical framework. Data were collected from GoTo’s annual and sustainability reports, regulatory documents, and relevant national and international scholarly literature. The findings indicate that GoTo demonstrates strong economic feasibility through job creation, financial inclusion, and MSME empowerment, reflecting the fulfillment of maslahah and hifz al-mal. Nevertheless, substantial environmental challenges persist, particularly related to transportation emissions, energy-intensive digital infrastructure, and packaging waste, indicating limited fulfillment of hifz al-bi’ah. The study concludes that integrating environmental sustainability into core business strategies and aligning corporate decision-making with maqashid al-shariah principles are essential to ensure the long-term feasibility and ethical legitimacy of digital platform businesses.